2008
DOI: 10.1111/j.1540-8167.2007.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Life‐Threatening Left Atrial Wall Hematoma Secondary to a Pulmonary Vein Laceration: An Unusual Complication of Catheter Ablation for Atrial Fibrillation

Abstract: Left atrial wall hematoma without pericardial effusion is a rare and life-threatening complication after catheter-based AF ablation. TEE is a valuable monitoring tool to accurately diagnose several acute complications and prompt rapid intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…To the present authors’ knowledge, this is the first reported case of left atrial intramural hematoma (LAIH) following ablation of a left posterolateral accessory pathway using a retrograde aortic approach. LAIH, also commonly referred to as left atrial dissection, has been most frequently associated with mitral valve repair and replacement (in more than one-half of cases) as well as post-RFA for atrial fibrillation and left atrial tachycardia ( 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ). Up to 10% of cases may occur spontaneously ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the present authors’ knowledge, this is the first reported case of left atrial intramural hematoma (LAIH) following ablation of a left posterolateral accessory pathway using a retrograde aortic approach. LAIH, also commonly referred to as left atrial dissection, has been most frequently associated with mitral valve repair and replacement (in more than one-half of cases) as well as post-RFA for atrial fibrillation and left atrial tachycardia ( 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ). Up to 10% of cases may occur spontaneously ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…This reflects rapid expansion of the mass with occlusion of left atrial inflow and outflow. Acute and unstable presentations almost always require prompt surgical relief of the obstruction ( 2 , 5 , 7 , 8 ). In a review by Fukuhara et al.…”
Section: Discussionmentioning
confidence: 99%
“…4 Mansour et al 5 reported the entrapment of a circular mapping catheter in the left superior PV that was successfully released with the use of the ablation catheter defl ectable tip to change the vector of traction. In another case by Echahidi et al, 6 an RIPV laceration with left atrial wall hematoma and hemodynamic instability required immediate surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Echahidi reported LA dissection secondary to a pulmonary vein laceration during catheter ablation. The patient was diagnosed with systemic lupus erythematosus and chronic kidney disease and had been treated with immunosuppressive and steroid medication, which might have caused friability of LA tissue [54]. Ninomiya reported a patient who underwent double valve replacement and tricuspid annuloplasty for aortic and mitral stenosis and tricuspid regurgitation after open mitral commissurotomy 26 years ago.…”
Section: Pathogenesismentioning
confidence: 98%